2011
DOI: 10.1007/s00035-010-0083-z
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic patterns of highland and lowland plant species in Japan

Abstract: As a result of ecological and historical factors, plant species occurring in mountainous regions often exhibit complex phylogeographical structure. The aim of this review is to identify the main phylogeographic patterns of plant species in the Japanese Archipelago, based on 63 previous studies; in particular, the intention is to examine the effects of mountains on these patterns. We classified species into three groups based on their distribution along altitudinal gradients: alpine and sub-alpine; montane; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 77 publications
1
20
0
Order By: Relevance
“…Quiroga and Premoli () suggested that Podocarpus parlatorei genetic decline toward higher elevations reflected forest migration during glacial periods. In the same way, Ohsawa and Ide () found that historical factors, rather than ecological ones, have primarily shaped intrapopulation genetic diversity distributions in montane species. The Serra do Mar mountain range formation began 65 million years ago (Hackspacher et al.…”
Section: Discussionmentioning
confidence: 79%
“…Quiroga and Premoli () suggested that Podocarpus parlatorei genetic decline toward higher elevations reflected forest migration during glacial periods. In the same way, Ohsawa and Ide () found that historical factors, rather than ecological ones, have primarily shaped intrapopulation genetic diversity distributions in montane species. The Serra do Mar mountain range formation began 65 million years ago (Hackspacher et al.…”
Section: Discussionmentioning
confidence: 79%
“…Long-distance migration in the past left traces of the genetic patterns of species, and in most cases, newly established marginal populations showed lower genetic diversity than long-standing populations (Bialozyt, Ziegenhagen, & Petit, 2006;Ohsawa & Ide, 2011;Waters, Fraser, & Hewitt, 2013). Yet the genetic pattern of some species, such as walnuts (Juglans spp.…”
Section: Persistence Both In the North And In The South Without Lonmentioning
confidence: 99%
“…A latitudinal decline in genetic diversity, especially in terms of allelic richness, has been commonly found in high-latitude Northern Hemisphere tree lineages (e.g. Comps et al, 2001;Marsico and Hellmann, 2009;Ohsawa and Ide, 2011). Yet there are exceptions to this general pattern.…”
Section: Introductionmentioning
confidence: 98%